Changes in heavy metal levels, reproductive characteristics, oxidative stress markers and testicular apoptosis in rams raised around thermal power plant - Akarsu, Serkan Ali; Turk, Gaffari; Arkali, Gozde; Ceribasi, Ali Osman; Yuce, Abrurrauf (Elsevier Science Inc, 2022)
Male reproductive dysfunction is one of the damages in the organism caused by heavy metals. In this study, it was aimed to investigate the changes in heavy metal levels in serum and testicular tissue, and serum hormone levels, epididymal spermatozoa characteristics, tissue oxidative stress levels, testicular histology and testicular apoptosis level in rams raised in remote and near regions of a thermal power plant. A total of 75 rams were divided into 3 groups according to the regions, where they were born and raised, being far [250 km distance, group 1 (control), n = 25], close (20 km distance, group 2, n = 25) and very close (10 km distance, group 3, n = 25) to the thermal power plant. The blood along with testis and epididymis tissues was taken from the animals after slaughtering. In addition, soil and water heavy metal analyzes were also performed. The highest levels of serum Al, Cr, As, Ag, Sn and testicular Al, V, Ni, Ag, Cd, Cr, As, Pb, and the lowest levels of serum Cu, testicular Cu and Zn were determined in group 3 compared to control. Soil and water heavy metal results were similar to those found in serum and testis. The lowest serum testosterone level, tissue glutathione-peroxidase and catalase activities, spermatozoon concentration, and the highest tissue malondialdehyde level, dead spermatozoon rate, Bax apoptotic protein expression level and Bax/Bcl-2 rate alongside some testicular histopathological lesions were found in group 3 in comparison to control. Significant correlations were determined between some heavy metal levels and some parameters measured. As a result, heavy metals accumulate in the soil and water in the region close to the thermal power plant. The endocrine and exocrine reproductive potentials of rams born and grown in these regions were clearly damaged by the increased testicular heavy metals due to water drank and herbs consumed. (c) 2021 Published by Elsevier Inc.
Keywords: Heavy metals; Oxidative stress; Ram; Spermatozoon; Thermal power plant; Testis